RANCANGAN SISTEM INFORMASI APLIKASI PENDATAAN ARSIP MEDIA BARU BERBASIS WEB MENGGUNAKAN METODE WATERFALL DI UNIT USDG PT KAI (PERSERO) - Yenni Fatman; Dina Marlisa Putri; Haryati Ona Farisa (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
Unit Corporate Document Management (USDG) is the archives unit I at PT Kereta Api Indonesia (Persero). Unit USDG carries out various tasks, one of which is the collection of data on new media archives. New media archive data collection is still done manually using Microsoft Excel. The current collection of data on new media archives system has several problems including: there is no resistance to duplicating agenda numbers, links to view files cannot be accessed, and user access rights to register new media archives have not been restricted. Information system design is needed to minimize problems and create new innovations for new media archive data collection systems. Qualitative method is the method used by the author. The author used the SWOT method to analyze the current collection of data on new media archives system and the Waterfall methode to develop a new system. Application web-based New Media Archive Data Collection is the result of this research. It is hoped that application can further optimize work new nedia archive data collection at Unit USDG.